2015
DOI: 10.1016/j.ijgo.2015.06.057
|View full text |Cite
|
Sign up to set email alerts
|

A randomized clinical trial of preoperative versus postoperative misoprostol in elective cesarean delivery

Abstract: Preoperative misoprostol (400μg, given rectally) reduces blood loss to a greater extent than does postoperative misoprostol during elective cesarean delivery. The frequency of complications was not affected by time of administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 13 publications
0
16
1
Order By: Relevance
“…A number of patients requiring additional uterotonic drugs were 38 in group 1 and 69 in group 2. Three patients in group 2 experienced blood loss of more than 1000 ml [22]. In contrast to our study, the total amount of blood loss in group 2 was much less than their study (656.76 ± 82.43 ml).…”
Section: Discussioncontrasting
confidence: 95%
“…A number of patients requiring additional uterotonic drugs were 38 in group 1 and 69 in group 2. Three patients in group 2 experienced blood loss of more than 1000 ml [22]. In contrast to our study, the total amount of blood loss in group 2 was much less than their study (656.76 ± 82.43 ml).…”
Section: Discussioncontrasting
confidence: 95%
“…Four studies 12,17,31,38 evaluated the preoperative misoprostol compared to postoperative misoprostol. These included 968 women (484 in each group).…”
Section: Preoperative Misoprostol Versus Postoperative Misoprostolmentioning
confidence: 99%
“…These advantages give misoprostol the priority to be the standard treatment for PPH in low resource areas. 17 A systemic evaluation of the use of misoprostol through different routes before and during CD is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Rectal misoprostol is associated with slower absorption, longer duration of action and minimal side effects, hence considered as best route for patient undergoing caesarean delivery. Rectal misoprostol administration has mean T-max of 40 -65 minutes (6,7) and recent study showed T-max of 20 minutes which is much shorter. (8) If rectal misoprostol administered before caesarean section, the maximum effect was obtained by the end of surgery, as there is slower rate of absorption which is useful.…”
mentioning
confidence: 98%
“…(8) If rectal misoprostol administered before caesarean section, the maximum effect was obtained by the end of surgery, as there is slower rate of absorption which is useful. (7,9) As there is wide gap of controversy in the results of many studies about the use of misoprostol for prevention of postpartum haemorrhage with caesarean section and also route of misoprostol administration was not fully studied; Hence this study was conducted to compare the effects of preoperative administration of rectal misoprostol with IM oxytocin on reducing blood loss in caesarean section and to study side effects.…”
mentioning
confidence: 99%